Observing the full ocean volume using Deep Argo floats - Zilberman, Nathalie V.; Thierry, Virginie; King, Brian; Alford, Matthew; André, Xavier; Balem, Kevin; Briggs, Nathan; Chen, Zhaohui; Cabanes, Cécile; Coppola, Laurent; Dall’Olmo, Giorgio; Desbruyères, Damien; et al. (Frontiers in Marine Science, 2023)
The ocean is the main heat reservoir in Earth’s climate system, absorbing most of the top-of-the-atmosphere excess radiation. As the climate warms, anomalously warm and fresh ocean waters in the densest layers formed near Antarctica spread northward through the abyssal ocean, while successions of warming and cooling events are seen in the deep-ocean layers formed near Greenland. The abyssal warming and freshening expands the ocean volume and raises sea level. While temperature and salinity characteristics and large-scale circulation of upper 2000 m ocean waters are well monitored, the present ocean observing network is limited by sparse sampling of the deep ocean below 2000 m. Recently developed autonomous robotic platforms, Deep Argo floats, collect profiles from the surface to the seafloor. These instruments supplement satellite, Core Argo float, and ship-based observations to measure heat and freshwater content in the full ocean volume and close the sea level budget. Here, the value of Deep Argo and planned strategy to implement the global array are described. Additional objectives of Deep Argo may include dissolved oxygen measurements, and testing of ocean mixing and optical scattering sensors. The development of an emerging ocean bathymetry dataset using Deep Argo measurements is also described.